1 0 5 1 1 2 6 1 2 3 7 1 3 ⋮ 1 4 8 1 4 9 1 5 1 6
Given that the pattern continues, find the second term in the 1 3 th row.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Log in to reply
0^2 --> 1^2 --> 2^2 --> 3^2 --> 4^2 --> 5^2 --> 6^2 --> 7^2 --> 8^2 --> ... Convert to numbers*
0 --> 1 --> 4 --> 9 --> 16 --> 25 --> 36 --> 49 --> 64 --> ...
( +1 +3 +5 +7 +9 +11 +13 +15 +17 )
See the pattern?
But as you request full-rational proof:
Note: (n + 1)^2 = n^2 + 1 + 2n
For any n x n to increase (n) by 1, what happens? Lets us increase just one (n). There we have n x ( n + 1 ), where the difference is just one "n". Increase the next n and we end up with ( n + 1 ) x ( n + 1 ) which leads to the note. Reduce the n^2 and that is the difference between n^2 and ( n + 1 )^ 2 ---> 2n + 1 .
If you ask why is the form of the last row like that:
The 1st digit in order is (1), 2nd is (2), 3rd is (3) and so on. Same position number, same number in the order. A row contains ammount of numbers as the position number ( because of the order of the structure ).
Edit: There were a few mistakes I made, now repaired.
nice solution.
Log in to reply
He said that first is 145. 13^2 gives the last number in the row.
Its actualy 123...DUUUUUUUUUUUUUUHH!
there should be a bracket like this (2k-1). Great work anyway.
tOO hard to solve anyway
Let
a
n
denote the first term in nth row and
S
n
be their sum.
S n = 1 + S n = 2 + 5 + ⋯ + a n 1 + 2 + 5 + ⋯ + a n
Subtracting and rearranging for a n gives:-
a n = 1 + ( n − 1 ) 2 ( 1 + 3 + 5 + ⋯ + (n-1) terms )
⟹ a n = ( n − 1 ) 2 + 1
Thus in general nth row contains ( n − 1 ) 2 + 1 , ( n − 1 ) 2 + 2 , ⋯ , ( n − 1 ) 2 + 2 n − 1
Hence 2nd term in 13th row is ( 1 3 − 1 ) 2 + 2 = 1 4 6 .
I came to the same conclusion, close formulas. a n = n 2 + 1 proof ( k + 1 ) 2 + 1 An for the number of members per column a n = 1 + 2 n where n is the row index
Central numbers are 1 3 7 13 therefore in nth row central number is n^2-n+1. In row 13 the central number is 169-13+1=157. The number of entries in each row are 1 3 5 7 so in the nth row there are 2n-1 entries. In row 13 that is 25. Therefore the row starts with 157-12=145 and so the second number is 146.
R - row index N - Number of elements in row
N= R+(R-1) Second element in row: R^2-(N-2)
Observe that the first number of the
n
th
row is given by
1
+ sum of first
n
−
1
odd numbers.
So, the first term of the
1
3
th
row is
1
+
(
1
3
−
1
)
2
=
1
+
1
4
4
=
1
4
5
. (Sum of first
n
odd numbers is
n
2
).
So, the second term of this row is 1 4 5 + 1 = 1 4 6 .
Now, why does the first term increase like that?
It is because each term increases by the next odd number. So, the first term of the succeeding row would have 2 terms more than the current one (difference between two consecutive odd numbers is 2).
observe the pattern is square numbers
1 line = 1
2 lines = 4
3 lines = 9
so at the end of the 12th row we are at 144, so the second entry in row thirteen is is just a simple as add 2, giving 146.
It is so hard
I was too lazy I just wrote it down but great explanation
Simple way is to work out 2 is added to every row. Add the first 12 odd digits then plus 2.
row 1's first number= 1 row2's first number= 2 row3's first number= 5 row4's first number= 10 . . . . row n's first number= n^2 - 2n + 2
Therefore row 13's first number= 169-26+2=145 Therefore row 13's second number= 145+1=146
Since Sn=n/2(2a+(n-1)d);
a=first element =1 ; d=difference of elements between two rows =2 ; n=no.of rows.
so here we have to find the 2nd element of 13th row. Therefore we will calculate till n=12;
so S12=12/2 ( 2+(12-1)*2)
S12=6*24=144;
so 2nd element from 144 i.e 146.
There are two more terms on every successive row than the previous and the first row contains one term. This allows us to deduce that there are 2 n + 1 terms on every ( n + 1 ) th row. The square number that succeeds a 2 can be represented as ( a + 1 ) 2 which equates to a 2 + 2 a + 1 . Therefore, the last term in every n th row = n 2 . Then, the last term on the 1 2 th row is 144. Add 2 to get the 2nd term on the 1 3 th row = 1 4 6 .
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: General Term Pattern Recognition
Notice that the last term on the n t h row is n 2 ( ∗ ) ,so the last term on the 1 2 t h row is 1 4 4 ,so the first term in the 1 3 t h is 1 4 5 ,and the 2 n d is 1 4 6 .
( ∗ ) proof:
After each down step,we add two columns.So the n t h row has 2 n − 1 terms,as the first has one column.As the number of the term determines its value,the last term on the n t h row is k = 1 ∑ n 2 k − 1 = n 2 ⋆ ,which is just the sum of how many terms there were.
Proof of ⋆ :
k = 1 ∑ n 2 k − 1 = 2 k = 0 ∑ n k − n = n ( n + 1 ) − n = n 2 + n − n = n 2